Computational identification of mutually homologous Zika virus miRNAs that target microcephaly genes. Issue 1 (1st January 2017) - McLean, Ewen; Bhattarai, Roshan; Hughes, Brandon W.; Mahalingam, Kuhanandha; Bagasra, Omar
ABSTRACT: Background Zika virus (ZIKV) has been associated with a variety of neuropathologies, including microcephaly. We hypothesize that ZIKV genes activate host microRNAs (miRNAs) causing dysfunctional development of human fetal brains. Objectives/methods A bioinformatics search for miRNA genome-wide binding sites in the prototypic ZIKV (strain MR766) was undertaken to hunt for miRNAs with significant similarities with MCPH genetic sequences responsible for inducing MCHP in human fetal brains. Results Six ZIKV miRNAs were found to share mutual homology with 12 MCPH genetic sequences responsible for inducing MCPH. Noteworthy was miR-1304, which expressed 100% identity to six different MCPH genes. Conclusions We suggest that following infection of fetal neurons ZIKV may modulate the action of various miRNAs, and miR-1304 in particular, resulting in microcephaly.